Proyecto arquitectónico y urbanístico para la relocalización de la escuela de carabineros Eduardo Cuevas García de Villavicencio. (2020)
According to “Plan de Ordenamiento Territorial de Villavicencio”, there is a need to relocate el “Departamento de Policía del Meta y La Escuela de Carabineros Eduardo Cuevas García”, and also the causes of it, so the object of study will then be to base relocation; and the subject will be to conceive the architectural project. Research throught a documentary methodological process, allows to collect necessary data to approach the variables that surround the project, starting the deductive method as an introspection, variables that will be studied in depth individually applying the analytical method, to expand the knowledge of the context, and in this way understand the relationships between them. Using the synthetic method, these variables will be ordered in such a way that they can be unite and synthesized, in order to use this information as guidelines, parameters, conditioners, determinants, and / or design criteria.